Activation of the Melanocortin-1 Receptor by NDP-MSH Attenuates Oxidative Stress and Neuronal Apoptosis through PI3K/Akt/Nrf2 Pathway after Intracerebral Hemorrhage in Mice. (12th November 2020) - Fu, Siming; Luo, Xu; Wu, Xuan; Zhang, Tongyu; Gu, Linggui; Wang, Yiying; Gao, Meng; Cheng, Yuan; Xie, Zongyi
Abstract : Oxidative stress and neuronal apoptosis play crucial roles in secondary brain injury (SBI) after intracerebral hemorrhage (ICH). Recently, Nle4-D-Phe7- α -melanocyte-stimulating hormone (NDP-MSH), a synthetic agonist of the melanocortin-1 receptor (Mc1r), has been proved to inhibit neuroinflammatory in several diseases. This study is aimed at exploring if NDP-MSH could reduce oxidative stress and neuronal apoptosis following ICH, as well as the potential mechanism. A mouse ICH model was induced by autologous blood injection. NDP-MSH was intraperitoneally injected at 1 h after ICH. Mc1r siRNA and PI3K inhibitor LY294002 were administrated to inhibit the expression of Mc1r and phosphorylation of PI3K, respectively. Neurological test, brain water content, enzyme-linked immunosorbent assay (ELISA), terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL), immunofluorescence, and Western blot analysis were utilized in this study. The results exhibited that Mc1r was mainly expressed in neurons, and its level in the ipsilateral hemisphere was significantly elevated after ICH. NDP-MSH treatment significantly attenuated the neurological deficits and brain water content 24 hours after ICH, which was accompanied by the inhibition of oxidative stress and neuronal apoptosis. The administration of NDP-MSH after ICH significantly promoted the expression of Mc1r, p-PI3K, p-Akt, and p-Nrf2, followed by an increase of Bcl-2 and reduction of cleaved caspase-3. Conversely, downregulating the expression of Mc1r and phosphorylation of PI3K aggravated the neurological deficits and brain edema at 24 hours after ICH, meanwhile, the effect of NDP-MSH on the expression of Mc1r, p-PI3K, p-Akt, p-Nrf2, Bcl-2, and cleaved caspase 3 was also abolished. In conclusion, our data suggest that the activation of Mc1r by NDP-MSH ameliorates oxidative stress and neuronal apoptosis through the PI3K/Akt/Nrf2 signaling pathway after ICH in mice.